Performance analysis of dielectric application methods in electrical discharge machining - Cogun, Can; Tosun, Nihat (Sage Publications Ltd, 2025)
A lack of comprehensive research exists on the machining performance of the reciprocating electrode method (REM) compared to other dielectric application methods (DAMs), particularly the commonly used side flushing method (SFM) in electric discharge machining. This study aims to investigate the performance outputs of the two methods under varying machining parameters through experimental and statistical analysis to fill the gap in the field. The impact of each machining parameter and DAM on the critical performance outputs was also determined using the analysis of variance (ANOVA). The study employed signal-to-noise ratio analysis to ascertain the optimal machining parameter settings. It has been demonstrated that the REM has several advantages over the SFM, including a 2-25% reduction in average surface roughness, a 5-70% decrease in electrode wear rate, a smoother workpiece surface, and sharper edges. However, the SFM exhibits a higher workpiece removal rate and less relative wear (RW) than the REM. The ANOVA revealed that the primary factor influencing the RW was the pulse time, followed by the discharge current and the DAM. Similarly, the discharge current was the primary factor affecting the average roughness and mean spacing between successive profile peaks, followed by the pulse time.
Keywords: Electric discharge machining; dielectric flushing; reciprocating electrode method; side flushing method; machining performance; analysis of variance